2004
DOI: 10.1111/j.1365-2419.2004.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the reproduction of three oncaeid copepods in the surface layer of the Kuroshio Extension

Abstract: Seasonal changes in reproduction rates of three dominant oncaeids, Oncaea media, O. venusta f. venella and O. venusta f. -1, and effects of environmental factors on them were examined in the surface layer (0-30 m) in the Kuroshio Extension and adjacent waters off the Pacific coast of central Japan. The biomass of oncaeid copepods peaked in spring, and remained at about 14% of total copepod biomass throughout the year. Monthly mean specific egg production rates of O. media, O. venusta f. -1 and O. venusta f. ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It can directly or indirectly impact the distribution of zooplankton, including copepod (Nakata et al 2004;Bigler et al 2006;Pipan et al 2006). The results showed that there was a positive correlation between diversity (0.01> P) and density (0.05> P) of copepods with temperature which is corresponded with increasing the density of copepods in summer and decreasing of them in winter.…”
Section: Resultsmentioning
confidence: 61%
“…It can directly or indirectly impact the distribution of zooplankton, including copepod (Nakata et al 2004;Bigler et al 2006;Pipan et al 2006). The results showed that there was a positive correlation between diversity (0.01> P) and density (0.05> P) of copepods with temperature which is corresponded with increasing the density of copepods in summer and decreasing of them in winter.…”
Section: Resultsmentioning
confidence: 61%
“…Nutrient supply to the surface after the spring stratification due to the turbulent mixing could lead to the high concentration of phytoplankton around the Kuroshio front, which would have an effect on the abundance of zooplankton (e.g., through effects on egg production as suggested by Nakata et al . []) and fishes, in particular larvae, which feed on zooplankton as reported previously [ Nakata et al ., ; Okazaki et al ., , ]. This may be one reason why the Kuroshio is an important nursery ground for many pelagic fishes.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller-bodied taxa such as clausocalanids appear to be less influenced by either warm or cold events (Hopcroft et al, 2002). However, Oncaea sp., which was abundant in surface waters during the strong upwelling event in 1999, showed higher abundance concomitant with increased primary production and lowered temperature (Nakata et al, 2004), like omnivores in field observations (Paffenhö fer, 1993). Doubling of the abundance of Oncaea spp.…”
Section: Discussionmentioning
confidence: 97%